Desire and Development - Holger Strulik (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper sets up a unified growth model and explores the impact of gender differences in the desire for sex and the distribution of power in the household for the onset of the demographic transition and the take-off to growth. Depending on the price and efficacy of modern contraceptives, the gender wage gap, and female bargaining power the model assumes one of two possible solutions. At the traditional equilibrium, contraceptives are not used, fertility is high and education and growth are low. At the modern equilibrium, contraceptives are used, fertility is low and further declining with increasing income, and education and growth are high. The theory motivates an endogenous preference reversal. At the traditional equilibrium (i.e. in poor economies) men want to have more children than women whereas at the modern equilibrium (in developed economies) men prefer fewer children than women. Female empowerment leads to lower fertility and more education at the traditional equilibrium and to an earlier onset of the demographic transition and the take-off to modern growth.
Keywords: O40; I25; J10; 330